2015
DOI: 10.1016/j.bbi.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory profiles in the BTBR mouse: How relevant are they to autism spectrum disorders?

Abstract: Autism spectrum disorders (ASD) are a group of disorders characterized by core behavioral features including stereotyped interests, repetitive behaviors and impairments in communication and social interaction. In addition, widespread changes in the immune systems of individuals with ASD have been identified, in particular increased evidence of inflammation in the periphery and central nervous system. While the etiology of these disorders remains unclear, it appears that multiple gene and environmental factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 61 publications
1
43
1
Order By: Relevance
“…BTBR mice have revealed a number of immune abnormalities several of which observed in children with ASD [21]. The neuroimmune relation in the BTBR mice is characterized by higher pro-inflammatory signaling and diminished social interactions [52,53]. BTBR mice showed the elevated expression levels of cytokines in the brain [24].…”
Section: Discussionmentioning
confidence: 98%
“…BTBR mice have revealed a number of immune abnormalities several of which observed in children with ASD [21]. The neuroimmune relation in the BTBR mice is characterized by higher pro-inflammatory signaling and diminished social interactions [52,53]. BTBR mice showed the elevated expression levels of cytokines in the brain [24].…”
Section: Discussionmentioning
confidence: 98%
“…The BTBR T + Itpr3 tf /J (BTBR) inbred mouse strain is a well characterized animal model exhibiting several behaviors relevant to the core features of ASD, including reduced social interactions, repetitive behavior, and atypical vocalizations (for review see (Careaga et al, 2015b)). Compared to the highly social C57BL/6J (C57) strain, BTBR mice exhibit heightened inflammatory phenotypes in the peripheral immune system and central nervous system, characteristics often reported in individuals with ASD (Careaga et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the highly social C57BL/6J (C57) strain, BTBR mice exhibit heightened inflammatory phenotypes in the peripheral immune system and central nervous system, characteristics often reported in individuals with ASD (Careaga et al, 2015b). For example, BTBR mice show signs of increased microglia activation (Heo et al, 2011), a marker of neuroinflammation also reported in individuals with ASD (Morgan et al, 2010; Suzuki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also demonstrated that children with ASD are more likely to have middle ear infections and otitis-related complications than healthy counterparts [3] . A dysregulated or abnormal immune response in children with ASD has been considered to play a potential and yet undetermined role in the etiology of autism [4,5] . Immune system abnormalities in children with autism include both enhanced autoimmunity and reduced immune function [6] .…”
Section: Resultsmentioning
confidence: 99%